Experiências de captação de recursos e a interface com o marketing social: estudo de caso Núcleo Social de Diadema - Teske, Rui Osvaldo (2014)
Many organizations of the Third Sector Brazilian act in the public interest by providing services to the population. On 23 March 1999, the Brazilian government approved the Law Nr. 9.790/99, allowing some of them to qualify as Civil Society Organizations of Public Interest - OSCIPs. Towards the State, that qualification implies many obligations, many of which are directly related with the organizational management, both when it comes to the application, and to the further execution of projects in partnership with public departments. The organizational relevance of this study concerns the potential benefits for the Social Center in Diadema upon learning which are the best fundraising strategies, ways, and possible partnerships through social marketing. By this, the Social Center could implement the suggestions herein in order to organize the activities of the institution and the duties of the employees. Therefore, the result will be greater satisfaction of the organization, exceeding the expectations and sustainability. The Social Center of Diadema needs a planning in order to obtain those resources, allowing a greater improvement perception related to the successful development of the growing institution, and enjoy the results of this work in order to achieve its goals